2015
DOI: 10.13189/aeb.2015.030804
|View full text |Cite
|
Sign up to set email alerts
|

The Relationships between Socio-demographic Variables, Travel Motivations and Subsequent Choice of Vacation

Abstract: This study explores the relationship between socio-demographic variables and travel motivation and further investigates how travel motivations influence the travelers' choice of vacation. The data were obtained using an internet-based questionnaire administered to a random sample of 256 respondents. Using factor analyses, six motivational factors, thematically similar to other studies on travel motivation, were identified. In contrast to previous research on travel motivations among travelers from other countr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
35
4

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(47 citation statements)
references
References 16 publications
8
35
4
Order By: Relevance
“…The H0 was confirmed because this study shows that motives for visit and constraints are different depending on sociodemographic characteristics of respondents. Results of this study are in accordance with previous research (Haukeland et al, 2010;Jensen, 2011;Kim et al, 2003), which also indicates that sociodemographic characteristics have an influence on motives for visit. Our study partially confirmed findings obtained by Ma et al (2018), which admittedly used other variables but came to conclusion that sociodemographic characteristics have significant impact on motivation for visiting national parks.…”
Section: Resultssupporting
confidence: 92%
“…The H0 was confirmed because this study shows that motives for visit and constraints are different depending on sociodemographic characteristics of respondents. Results of this study are in accordance with previous research (Haukeland et al, 2010;Jensen, 2011;Kim et al, 2003), which also indicates that sociodemographic characteristics have an influence on motives for visit. Our study partially confirmed findings obtained by Ma et al (2018), which admittedly used other variables but came to conclusion that sociodemographic characteristics have significant impact on motivation for visiting national parks.…”
Section: Resultssupporting
confidence: 92%
“…Kim et al [17] also suggested that younger people are more motivated by novelty seeking than older people. For young people, it was reported that "recreation/physical activities", "enjoying nature", "prestige and impression" and "social seeking" were more important motivational factors [17,20,36,37]. Concerning the education level of tourists, more-educated tourists were suggested to be motivated more by "relax and escape", "knowledge seeking" and "socialization", while less-educated people were more associated with the factors of "prestige/impression" and "novelty" [17,37].…”
Section: Literature Reviewmentioning
confidence: 99%
“…For young people, it was reported that "recreation/physical activities", "enjoying nature", "prestige and impression" and "social seeking" were more important motivational factors [17,20,36,37]. Concerning the education level of tourists, more-educated tourists were suggested to be motivated more by "relax and escape", "knowledge seeking" and "socialization", while less-educated people were more associated with the factors of "prestige/impression" and "novelty" [17,37]. In terms of income, tourists in higher income groups rated the "appreciation of nature" and "escape and relaxation" as more important, while those in lower income groups showed a stronger preference for "knowledge seeking" [17,37].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Few of those who reported that the HRE had occurred overseas in the country in which they were born were recent arrivals to Australia. The association between higher education level and overseas travel is likely to be a function of education being a distal proxy for income, desire and opportunity to travel more frequently and for longer periods of time …”
Section: Discussionmentioning
confidence: 99%